2010
DOI: 10.4319/lo.2010.55.6.2463
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of selection for resistance to paralytic shellfish toxins during the early life history of soft‐shell clam, Mya arenaria, populations

Abstract: This study identifies early, postmetamorphic soft-shell clams, Mya arenaria, as the life-history stage most susceptible to effects of blooms of paralytic shellfish poisoning (PSP) toxin-producing Alexandrium spp. Laboratory experiments used progeny from predominantly susceptible (naïve) or resistant (annually exposed) NW Atlantic populations. Growth and survival of toxified veliger larvae did not differ from those fed nontoxic algae. In contrast, postlarvae (4-12-mm shell length) from both populations exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…This agrees with prior findings that mortalities of subadult Mya arenaria (33 to 47 mm SL) typically started only after ~1 to 2 wk of exposure to 100 cells ml -1 of the same isolate (MacQuarrie & Bricelj 2008). Greater vulnerability to PSTs of small clams was also demonstrated when burrowing and survival were compared between Mya arenaria~12 mm and 35 mm SL exposed to comparable toxin concentrations (Bricelj et al 2010). Burrowing capacity is a critically important fitness parameter that is likely under strong natural selection, especially in juvenile bivalves before they attain a size refuge from predators.…”
Section: Effects Of Psts On Burrowing Capacity Of Ruditapes Philippinsupporting
confidence: 90%
See 2 more Smart Citations
“…This agrees with prior findings that mortalities of subadult Mya arenaria (33 to 47 mm SL) typically started only after ~1 to 2 wk of exposure to 100 cells ml -1 of the same isolate (MacQuarrie & Bricelj 2008). Greater vulnerability to PSTs of small clams was also demonstrated when burrowing and survival were compared between Mya arenaria~12 mm and 35 mm SL exposed to comparable toxin concentrations (Bricelj et al 2010). Burrowing capacity is a critically important fitness parameter that is likely under strong natural selection, especially in juvenile bivalves before they attain a size refuge from predators.…”
Section: Effects Of Psts On Burrowing Capacity Of Ruditapes Philippinsupporting
confidence: 90%
“…1). The Alexandrium tamarense exposure concentration was selected based on prior experiments with juvenile (4 mm) Mya arenaria, in which 100 cells ml -1 caused severe mortalities, 10 cells ml -1 had no effect on survival or growth, although it affected motility, and 50 cells ml -1 caused 15% mortalities by the end of 2 wk and severe growth inhibition (Bricelj et al 2010). Cell densities of A. tamarense in the experimental tanks were determined microscopically and those of Isochrysis galbana were determined with an electronic Coulter counter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutation allows nerve transmission to occur normally in resistant animals even under toxic food conditions (Bricelj et al, 2005); resistant clams outcompete susceptible individuals and predominate in areas where toxic Alexandrium spp. occur (Bricelj et al, 2010;Connell et al, 2007). Similar mutations confer resistance to tetrodotoxin, a toxin that also blocks sodium channels, in snakes (Geffeney et al, 2002) and pufferfish (Venkatesh et al, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Twarog (1974) also theorized that recurrently exposed shellfish populations may undergo a genetic adaptation to PSTs with natural selection against individuals sensitive to the toxins. Research on the soft-shelled clam ( Mya arenaria ) has shown an adaptation in clam populations from geographical regions with prior history of exposure to PSTs where the substitution of a single amino acid can confer resistance to STX (Bricelj et al, 2005; Connell et al, 2007; MacQuarrie and Bricelj, 2008; Bricelj et al, 2010). The specific substitution elucidated in in M. arenaria was a simple change from adenine (A) to cytosine (C) in the domain II pore region of the alpha-subunit of the voltage-gated Na + channel (Bricelj et al, 2005).…”
Section: Introductionmentioning
confidence: 99%